2020
DOI: 10.1007/s12079-020-00554-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody against osteopontin attenuates non-alcoholic steatohepatitis in mice

Abstract: Previously, we reported that an extracellular matrix protein, osteopontin (OPN), is involved in various autoimmune diseases using a neutralizing polyclonal antibody against OPN generated in rabbits. However, the antibody cannot be used for long-term mouse models of chronic inflammatory disease because of the induction of antibodies against anti-OPN rabbit IgG. In this study, we generated a new antibody, anti-mouse OPN mouse IgG (35B6). 35B6 inhibited the cell adhesion of mouse and human OPN to Chinese Hamster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…This could suggest that hepatic LAMs drive the progression to NASH. Indeed, recent studies blocking osteopontin in mice models of NASH have suggested a protective effect ( Coombes et al., 2016 ; Honda et al., 2020 ; Kiefer et al., 2010 ). Unfortunately, to date, we do not have the tools to target this population specifically to address these questions, but generating these is an important aim for the future.…”
Section: Discussionmentioning
confidence: 99%
“…This could suggest that hepatic LAMs drive the progression to NASH. Indeed, recent studies blocking osteopontin in mice models of NASH have suggested a protective effect ( Coombes et al., 2016 ; Honda et al., 2020 ; Kiefer et al., 2010 ). Unfortunately, to date, we do not have the tools to target this population specifically to address these questions, but generating these is an important aim for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated the importance of cancer-TAM-CAF interactions via OPN for the first time. It has been suggested that OPN inhibitors might be useful in the prevention and treatment of hepatic inflammation and fibrosis in NASH [ 50 ]. Therefore, OPN might have potential as a new therapeutic target to inhibit cancer-CAF-TAM interactions in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a pro-fibrogenic role for OPN, it also has several pro-inflammatory properties targeting several innate immune cell populations including macrophages, neutrophils and natural killer cells [ 19 ]. A recent study in a murine NASH model demonstrated that antibodies targeting OPN not only attenuated fibrosis but also inflammation, suggesting that targeting OPN in the early stages of NAFLD may be effective in preventing the progression to NASH and fibrosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%